Association Between Midwall Late Gadolinium Enhancement and Sudden Cardiac Death in Patients With Dilated Cardiomyopathy and Mild and Moderate Left Ventricular Systolic Dysfunction. Issue 22 (30th May 2017) - Halliday, Brian P.; Gulati, Ankur; Ali, Aamir; Guha, Kaushik; Newsome, Simon; Arzanauskaite, Monika; Vassiliou, Vassilios S.; Lota, Amrit; Izgi, Cemil; Tayal, Upasana; Khalique, Zohya; Stirrat, Colin; et al.
Abstract : Background: Current guidelines only recommend the use of an implantable cardioverter defibrillator in patients with dilated cardiomyopathy for the primary prevention of sudden cardiac death (SCD) in those with a left ventricular ejection fraction (LVEF) <35%. However, registries of out-of-hospital cardiac arrests demonstrate that 70% to 80% of such patients have an LVEF >35%. Patients with an LVEF >35% also have low competing risks of death from nonsudden causes. Therefore, those at high risk of SCD may gain longevity from successful implantable cardioverter defibrillator therapy. We investigated whether late gadolinium enhancement (LGE) cardiovascular magnetic resonance identified patients with dilated cardiomyopathy without severe LV systolic dysfunction at high risk of SCD. Methods: We prospectively investigated the association between midwall LGE and the prespecified primary composite outcome of SCD or aborted SCD among consecutive referrals with dilated cardiomyopathy and an LVEF ≥40% to our center between January 2000 and December 2011 who did not have a preexisting indication for implantable cardioverter defibrillator implantation. Results: Of 399 patients (145 women, median age 50 years, median LVEF 50%, 25.3% with LGE) followed for a median of 4.6 years, 18 of 101 (17.8%) patients with LGE reached the prespecified end point, compared with 7 of 298 (2.3%) without (hazard ratio [HR], 9.2; 95% confidence interval [CI], 3.9–21.8; P <0.0001). Nine patients (8.9%) with LGE compared with 6 (2.0%) without (HR, 4.9; 95% CI, 1.8–13.5; P =0.002) died suddenly, whereas 10 patients (9.9%) with LGE compared with 1 patient (0.3%) without (HR, 34.8; 95% CI, 4.6–266.6; P <0.001) had aborted SCD. After adjustment, LGE predicted the composite end point (HR, 9.3; 95% CI, 3.9–22.3; P <0.0001), SCD (HR, 4.8; 95% CI, 1.7–13.8; P =0.003), and aborted SCD (HR, 35.9; 95% CI, 4.8–271.4; P <0.001). Estimated HRs for the primary end point for patients with an LGE extent of 0% to 2.5%, 2.5% to 5%, and >5% compared with those without LGE were 10.6 (95% CI, 3.9–29.4), 4.9 (95% CI, 1.3–18.9), and 11.8 (95% CI, 4.3–32.3), respectively. Conclusions: Midwall LGE identifies a group of patients with dilated cardiomyopathy and an LVEF ≥40% at increased risk of SCD and low risk of nonsudden death who may benefit from implantable cardioverter defibrillator implantation. Clinical Trial Registration: URL:http://clinicaltrials.gov . Unique identifier: NCT00930735. Abstract : Supplemental Digital Content is available in the text.